Alumni series: functionalism, pharmacists and pharmacy / Siti Hajar Mahamad Dom and Zahirah Zaharuddin - Mahamad Dom, Siti Hajar; Zaharuddin, Zahirah (Faculty of Pharmacy, 2023)
The functionalist theory views society as parts of a system that has specific functions. These parts work together to ensure that social order and stability are maintained. The famous sociologists that contributed to the functionalist theory include Herbet Spencer, Emile' Durkheim, Robert Merton and Talcott Parson. Herbert Spencer, an English philosopher and biologist, views functionalism of having similarities between society and the human body. Society is seen as a whole, in the aspect of functions of its institution's elements. An analogy that was famously introduced by Herbet Spencer explains our body consists of organs. Each organ has a vital function that is important for our body to work just like each part of society. If any of the organs fails to function, our body will malfunction and possibly die. Talcott Parsons, one of the most significant American functionalist sociologists of the 20th century emphasised the concept of dynamic equilibrium, which refers to how society creates social stability. He recognised the four functional subsystems and the functions they serve in society. The subsystems include economic, political, family, and cultural subsystems. These subsystems act not just for their own sake but also to enable the proper operation of the other subsystems.